Immunomodulation by adoptive regulatory T‐cell transfer improves Coxsackievirus B3‐induced myocarditis. Issue 11 (4th June 2018) - Pappritz, Kathleen; Savvatis, Konstantinos; Miteva, Kapka; Kerim, Bahtiyar; Dong, Fengquan; Fechner, Henry; Müller, Irene; Brandt, Christine; Lopez, Begońa; González, Arantxa; Ravassa, Susana; Klingel, Karin; et al.
ABSTRACT: Regulatory T (Treg ) cells offer new therapeutic options for controlling undesired systemic and local immune responses. The aim of the current study was to determine the impact of therapeutic Treg administration on systemic and cardiac inflammation and remodeling in coxsackievirus B3 (CVB3) ‐induced myocarditis. Therefore, syngeneic Treg cells were applied intravenously in CVB3‐infected mice 3 d after infection. Compared with CVB3 + PBS mice, CVB3 + Treg mice exhibited lower left ventricle (LV) chemokine expression, accompanied by reduced cardiac presence of proinflammatory Ly6C high CCR2 high Cx3Cr1 low monocytes and higher retention of proin flammatory Ly6C mid CCR2 high Cx3Cr1 low monocytes in the spleen. In addition, splenic myelopoiesis was reduced in CVB3 + Treg compared with CVB3 + PBS mice. Coculture of Treg cells with splenocytes isolated from mice 3 d post‐ CVB3 infection further demonstrated the ability of Treg cells to modulate monocyte differentiation in favor of the anti‐inflammatory Ly6C low CCR2 low Cx3Cr1 high subset. Treg ‐mediated immunomodulation was paralleled by lower collagen 1 protein expression and decreased levels of soluble and insoluble collagen in LV of CVB3 + Treg compared with CVB3 + PBS mice. In agreement with these findings, LV systolic and diastolic function was improved in CVB3 + Treg mice compared with CVB3 + PBS mice. In summary, adoptive Treg transfer in the inflammatory phase of viral‐induced myocarditis protects the heart against inflammatory damage and fibrosis via modulation of monocyte subsets.—Pappritz, K., Savvatis, K., Miteva, K., Kerim, B., Dong, F., Fechner, H., Müller, I., Brandt, C., Lopez, B., González, A., Ravassa, S., Klingel, K., Diez, J., Reinke, P., Volk, H.‐D., Van Linthout, S., Tschöpe, C. Immunomod ulation by adoptive regulatory T‐cell transfer improves Coxsackievirus B3‐induced myocarditis. FASEB J . 32, 6066–6078 (2018). www.fasebj.org